Power Amplifiers and Antennas for Implantable Biomedical Transceivers - Abdelsayed, Samar (My University, 2006)
Recently, there has been a strong trend in medicine to use implanted electronic devices for diagnostic and/or therapeutic purposes. These devices usually involve a one- or twoway communication link, allowing communication with the implant. One revolutionary implanted system that was recently launched into the healthcare market is the wireless imaging capsule for monitoring the gastrointestinal tract. Among the application-specific design challenges of such a wireless system are the severe constraints on low power and on small physical size. Besides, the allowed power levels of signals due to in-body radiating devices are restricted to very low values due to human safety concerns. To meet the requirements of such a wireless system, highly efficient, small-size, low-power transmitting radio frequency (RF) blocks are needed.
This thesis focuses on the design, implementation and measurements of the last two blocks in the transmitter, namely the antenna and the power amplifier (PA). Three PA circuits have been designed and measured, all of class AB topology. The first two PAs operate at 2.4 GHz, while the third is designed for 405-MHz operation. All designs are fully integrated and realized in a standard mixed-signal 0.18 ~m complementary metaloxide- semiconductor (CMOS) process. Measurement results show that at a supply voltage of 1.4 V, the circuits have a maximum drain efficiency of 32% and 40.7% for the 2.4-GHz and the 405-MHz designs, respectively, while providing an output power of 7.2 and 8 dBm to the load. These results greatly outperform similar designs in the literature, proving that class AB PAs, if properly designed, are well-suited for low-power biotelemetry application.
A simple layout design approach was developed to minimize the parasitic effects of on-silicon interconnections that cause significant degradation in the performance of RF integrated circuits (RF ICs ). This approach was used to design the layouts of the three PA circuits presented in this work, and the approach was tested on a low-noise amplifier (LNA) operating at 5 GHz, since at such a high frequency the parasitics become more pronounced. Measurements on the LNA circuit show good agreement with simulations.
Thus, next to allowing for optimized circuit performance, this approach can shorten the design time of RF ICs by providing very good predictions of performance characteristics.
The last part of this thesis deals with the analysis and design of efficient in-body antennas. A study of the use of loop antennas in medical implants was conducted. Simulations and measurements have been used to characterize the radiation performance of loop antennas in terms of their radiation resistance, transmitting bandwidth and biocompatibility. At 405 MHz, the antenna has proven to be efficient in the dissipative biological tissues, to have a wide transmitting bandwidth, and a specific absorption rate (SAR) distribution that is well below the safety limits. To further verify its suitability for in-body operation, a miniature loop antenna was fabricated and measured at 405 MHz and 2.4 GHz. For measurement purposes, two body simulating chemical solutions were prepared in-house to provide the necessary radiation environment. Measurements show that small loop antennas are well matched in the medium and are thus good in-body radiators.
Keywords: Power Amplifiers; Antennas; Biomedical Transceivers